Hybrid Steepest Descent Viscosity Method for Triple Hierarchical Variational Inequalities - L.-C. Ceng; Q. H. Ansari; C.-F. Wen (Abstract and Applied Analysis)
We consider a triple hierarchical variational inequality problem (in short, THVIP). By combining hybrid steepest descent method, viscosity method, and projection method, we propose an approximation method to compute the approximate solution of THVIP. We also study the strong convergence of the sequences generated by the proposed method to a solution of THVIP.